Eucalyptus Trees Plantation: A Review on Suitability and their Beneficial Role - Kaur, Amanpreet; Monga, Rajesh (International Journal of Bio-resource and Stress Management, 2021)
Eucalyptus is fastest growing species popularly known as gum tree, red iron tree, safeda and belonging to the family Myrtaceae. E. tereticornis and E. grandis are important commercial species with a clean straight bole and compact crown. Large scale plantations have been raised on forest and farm lands, community lands, field boundaries and road/rail/canal strips in India. It is most suitable species for degraded land, waterlogged areas, problematic soils etc. Although, it is a controversial tree because of high water consumption, nutrient depletion, allopathic effects etc., it is also source of pulp, paper, essential oil, timber, medicinal use, etc. Moreover it also provides ecological, socioeconomic and industrial services. Improvement in physical and chemical properties of on Sodic wastelands, heavy metal accumulation in different tissues of in mined soil; carbon sequestration potential, etc. were reported in studies. On unit basis of dry biomass produced, it consumes very little water compared to other trees. If bark of the tree is left on site, the balance of nutrients remaining is (80-88%) of inputs for N, P, K, Ca and Mg which lasts for several years without considering the original nutrients that are still present in soil. In the face of growing economy and increased demand for wood products, it remains to be the desired species that grows fast and produce wood to meet the demand of wood for fuel, construction and furniture materials. Relieving wood product scarcity, landscape re-greening, contribution to poverty reduction, biodiversity restoration and conservation are valuable contribution in forest sector.